A glucose transport protein expressed predominately in insulin-responsive tissues. - Charron, M J (1989)
Using low-stringency hybridization to the rat brain glucose transporter (GT), a 2489-base-pair cDNA clone was isolated from a rat soleus lambda gt10 cDNA library. It encodes a 509-amino acid protein whose sequence and predicted membrane structure is very similar to those of the rat brain and liver GTs. The muscle GT-like protein is 65% identical in amino acid sequence to the rat brain GT and 52% identical to the rat liver GT; the major differences are in the NH2- and COOH-terminal hydrophilic segments. This GT-like mRNA is expressed predominately in tissues where glucose transport is sensitive to insulin, including striated muscle, cardiac muscle, and adipose tissue; low-level expression is also detected in smooth muscle and kidney mRNA. This GT-like cDNA is the fourth member of the mammalian GT-related gene family identified to date. We propose that it encodes an insulin-sensitive GT.